Intervoice: A Photovoice Project Intergenerational - Nunes, Raquel (2019)
This article describes an Intergenerational Photovoice Project implemented in a Residential Structure for the Elderly (ERPI), in Portugal, in which four elderly people and four university students participated. The Project consisted of asking the elderly and intergenerational peers to photograph the surrounding reality. Analyzing its impact on each participant in terms of very beneficial effects suggests that this may be a successful strategy for improving interpersonal, intergenerational relationships, and the physical and psychological well-being of especially institutionalized older people.